2011
DOI: 10.1186/2045-709x-19-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of the measure your medical outcome profile (MYMOP2) and W-BQ12 (Well-Being) outcomes measures to evaluate chiropractic treatment: an observational study

Abstract: BackgroundThe objective was to assess the use of the Measure Yourself Medical Outcome Profile (MYMOP2) and W-BQ12 well-being questionnaire for measuring clinical change associated with a course of chiropractic treatment.MethodsChiropractic care of the patients involved spinal manipulative therapy (SMT), mechanically assisted techniques, soft tissue therapy, and physiological therapeutic devices.Outcome measures used were MYMOP2 and the Well-Being Questionnaire 12 (W-BQ12).ResultsStatistical and clinical signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…15 MYMOP-2 scale is routinely used in studies of long-term conditions. 22,23 In this study, patients were asked to volunteer the most troublesome symptom associated with their condition, a problem related to activity and their overall well-being on a seven-point numerical rating scale. It was found that each and every patient shown improvement in all three domains and the improvements were statistically significant after 6 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…15 MYMOP-2 scale is routinely used in studies of long-term conditions. 22,23 In this study, patients were asked to volunteer the most troublesome symptom associated with their condition, a problem related to activity and their overall well-being on a seven-point numerical rating scale. It was found that each and every patient shown improvement in all three domains and the improvements were statistically significant after 6 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The MYMOP2 asks patients to identify their most important symptoms or complaints and rate the severity of the problems. It also asks how they feel about their general wellbeing, how long they have suffered from the problematic symptoms, and whether they take any drugs to attenuate those symptoms [37]. …”
Section: Methodsmentioning
confidence: 99%
“…52 The GRACE checklist is designed to guide the assessment of observational studies of comparative effectiveness in terms of their quality and usefulness for decision-making. 12,13 the Glasgow Homeopathic Hospital Outcome Scale (GHHOS), 42 the Measure Yourself Medical Outcome Profile (MYMOP), [43][44][45] the intensity of symptoms on a numeric rating scale, 12,13 and Outcome Related to Impact on Daily Living (ORIDL, formerly referred to as GHHOS). 46 In retrospective outcome studies, your random sample of medical records will enable you to get an overview of documented outcomes and quality of documentation before planning in more detail.…”
Section: Gracementioning
confidence: 99%